2014
DOI: 10.5173/ceju.2014.03.art17
|View full text |Cite
|
Sign up to set email alerts
|

Mesh–related and intraoperative complications of pelvic organ prolapse repair

Abstract: IntroductionTo evaluate the rates of complications of pelvic organ prolapse repair and to determine their risk factors.Material and methodsThe study included 677 patients operated for pelvic organ prolapse with trocar guided Prolift mesh. Patients were followed up within 1 and 3 months. A phone interview was conducted and patients with complaints were invited and evaluated in office settings.ResultsMean age was 60 years. For the phone interview, 86.5% of patients were available. Overall complication rates were… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

2
34
1

Year Published

2016
2016
2022
2022

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 36 publications
(39 citation statements)
references
References 17 publications
(18 reference statements)
2
34
1
Order By: Relevance
“…Concerns that the tape may shrink, lose strength, or change properties over time and thereby cause pain have been discussed [18]. Our study found no evidence suggesting that a TVT operation would lead to increased pain during sexual intercourse (question 5 in PISQ-12).…”
Section: Discussioncontrasting
confidence: 61%
“…Concerns that the tape may shrink, lose strength, or change properties over time and thereby cause pain have been discussed [18]. Our study found no evidence suggesting that a TVT operation would lead to increased pain during sexual intercourse (question 5 in PISQ-12).…”
Section: Discussioncontrasting
confidence: 61%
“…However, TVM showed favorable results with respect to the total cost and length of stay despite its performance by low‐volume hospitals. Previous studies have shown that the blood transfusion rate during TVM surgery was between 0 and 2.3% . These data show that the blood transfusion rate during TVM surgery in Japan tends to be low.…”
Section: Discussionsupporting
confidence: 53%
“…To further support pelvic tissues, surgical mesh constructs, i.e., polypropylene (PP), were rapidly introduced. However, US Food and Drug Administration (FDA) Public Health Notifications [4] have alerted clinicians to adverse events associated with PP mesh for vaginal repair surgery are not rare [2,[5][6][7]. This has led to withdrawal from the market of several widely used brands of vaginal mesh and looming class-action litigation.…”
Section: Introductionmentioning
confidence: 99%